One Size Does Not Fit All: Variability in Urinary Symptoms and Microbial Communities - Hochstedler-Kramer, Baylie; Joyce, Cara; Abdul-Rahim, Omar; Barnes, Hayley C.; Mueller, Elizabeth R.; Wolfe, Alan J.; Brubaker, Linda; Burnett, Lindsey A. (Frontiers in Urology, 2022)
The discovery of the urinary microbiome prompted researchers to begin characterizing microbiota associated with various health and disease states; however, the etiology of bladder infections, the most common urinary tract infection (UTI), is still simplistically attributed to the invasion of a uropathogen, mainly Escherichia coli, without regard for the resident microbial community. In addition, the clinical variability of UTI symptoms remains poorly understood. Very little research has been done to investigate the role of baseline microbial communities in development and resolution of UTI symptoms. The goal of this study was to identify associations between urinary microbiota and lower urinary tract symptoms profiles in adult women with UTI symptoms. This is a secondary analysis of a previously published IRB-approved study that included 225 women who reported having acute UTI symptoms and submitted catheterized urine specimens for analysis by an enhanced urine culture method and were assessed for symptom resolution 7-10 days after receiving culture-directed antibiotic treatment. In this UTI population, we identified six distinct symptom profiles, termed symptotypes, that were characterized by varying severity and degree of bother of certain lower urinary tract symptoms. These symptotypes were not associated with urotype or the presence of specific microbes. In participants with UTI pain on presentation, the presence of non-E. coli and non-uropathogens was associated with persistence of symptoms at follow up; however, this was not true for those with E. coli urotype. These data suggest that the presence of E. coli may insufficiently account for the underlying cause of typical UTI symptoms; instead, co-existence of a uropathogen in the context of the existing urinary microbiota and the host may be responsible for these symptom profiles.